Hydrogen solid-state secondary battery with vanadium-based positive electrode
By using vanadium-based compounds as the positive electrode material, combined with the Pt/C negative electrode and clay in the acid electrolyte, the problem of low specific capacity of the positive electrode material of the hydrogen battery is solved, and the high specific capacity and excellent performance of the hydrogen solid secondary battery are achieved, which is suitable for large Scale application.
Patent Information
- Application Number
- CN202411380125.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
AI Technical Summary
The existing hydrogen battery has a lower specific capacity of positive electrode materials, which limits its large-scale application.
Vanadium-based compounds are used as the positive electrode materials, including Li3V2(PO4)3, LiV3O8 and LiVOPO4, and combined with the Pt/C negative electrode and clay in the acidic electrolyte, a hydrogen solid secondary battery with a vanadium-based positive electrode is formed.
It realizes excellent cycle stability, high rate performance and low temperature performance of hydrogen solid secondary batteries, improves specific capacity, and is simple in preparation, has less energy consumption and low cost, which is suitable for industrialization.
Smart Images

Figure CN119230896A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery energy storage, and in particular to a hydrogen solid-state secondary battery with a vanadium-based positive electrode. Background Art
[0002] Aqueous secondary batteries use water-based electrolytes and have the characteristics of high safety, high power density and environmental friendliness, making them one of the most promising energy storage technologies. However, existing aqueous battery technologies, such as lead-acid, nickel-metal hydride and flow batteries, still face challenges in terms of environment, resources, cycle life and other issues. Therefore, it is extremely important to explore environmentally friendly, low-cost, highly safe and long-cycle-life aqueous secondary batteries.
[0003] Since 2018, Wei Chen et al. have reported a series of new aqueous secondary batteries - hydrogen batteries. + As a carrier (with the smallest ion radius), it has the fastest conduction rate in the electrolyte, which makes the battery have excellent rate performance. The hydrogen negative electrode can match different positive electrodes, such as the hydrogen negative electrode can match the insertion / extraction type positive electrode. Nickel hydrogen (Ni-H2) batteries, Prussian blue (PBA)-H2 batteries and lithium manganese oxide hydrogen (LMO-H2) batteries have been developed in alkaline, acidic and neutral electrolytes respectively. Among them, the nickel hydroxide positive electrode of the Ni-H2 battery has a low abundance in the earth's crust, and the PBA positive electrode material in the PBA-H2 battery and the lithium manganese oxide in the LMO-H2 battery have low specific capacity, which limits their large-scale application.
[0004] In summary, it is of great significance and value to find a positive electrode material with high specific capacity that can fully utilize the advantages of proton electrodes to construct hydrogen solid-state secondary batteries. Summary of the invention
[0005] In view of this, the present invention provides a hydrogen solid-state secondary battery with a vanadium-based positive electrode to solve the problem of low specific capacity of existing positive electrode materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a hydrogen solid-state secondary battery with a vanadium-based positive electrode, comprising a vanadium-based compound positive electrode, a Pt / C negative electrode and a solid electrolyte; the solid electrolyte comprises an acidic electrolyte and clay; the vanadium-based compound positive electrode comprises one of a Li3V2(PO4)3 positive electrode, a LiV3O8 positive electrode and a LiVOPO4 positive electrode.
[0008] Preferably, the preparation method of the Li3V2(PO4)3 positive electrode comprises the following steps: mixing a vanadium source, a lithium source, a phosphate source and water, heating to obtain a gel-like mixture, and calcining the gel-like mixture to obtain a Li3V2(PO4)3 positive electrode.
[0009] Preferably, the mass volume ratio of the vanadium source, lithium source, phosphoric acid source and water is 0.1-0.4g:0.1-0.3g:0.3-0.4g:6-10mL; the vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 one or more of the following: the lithium source comprises LiOH·H2O and / or LiNO3; the phosphoric acid source comprises one or more of NH4H2PO4 and (NH4)2HPO4; the heating step comprises: mixing the vanadium source, the lithium source, the phosphoric acid source and water, heating the mixture to 70-100°C, keeping the mixture warm for 8-14 hours, then adjusting the mixture to a vacuum environment, heating the mixture to 70-100°C, and keeping the mixture warm for 8-14 hours; the calcining step comprises: heating the gel-like mixture to 300-500°C, keeping the mixture warm for 2-8 hours, then adjusting the mixture to an argon atmosphere, heating the mixture to 700-950°C, and keeping the mixture warm for 8-10 hours.
[0010] Preferably, the preparation method of the LiV3O8 positive electrode comprises the following steps: mixing a vanadium source and a lithium source, and sequentially performing ball milling and calcination to obtain a LiV3O8 positive electrode.
[0011] Preferably, the mass ratio of the vanadium source to the lithium source is 2-4:0.3-1; the vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 One or more of the following: the lithium source comprises LiOH·H2O and / or LiNO3; the calcination temperature is 450-700°C and the calcination time is 8-10h.
[0012] Preferably, the preparation method of the LiVOPO4 positive electrode comprises the following steps: mixing a vanadium source, oxalic acid, a lithium source, a phosphoric acid source and water, and reacting to obtain a LiVOPO4 positive electrode.
[0013] Preferably, the mass volume ratio of the vanadium source, oxalic acid, lithium source, phosphoric acid source and water is 0.5-1.2g:1.5-2.5g:0.2-1g:0.75-1.50g:100-150mL; the vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 The lithium source includes LiOH·H2O and / or LiNO3; the phosphoric acid source includes one or more of NH4H2PO4 and (NH4)2HPO4; the reaction temperature is 350-550°C and the reaction time is 8-10h.
[0014] Preferably, the mass ratio of the acidic electrolyte to the clay in the solid electrolyte is 0.5-1.5:1-5; and the Pt in the Pt / C negative electrode accounts for 15%-50% of the total mass of the Pt / C negative electrode.
[0015] Preferably, the volume concentration of the acidic electrolyte is 10% to 85%.
[0016] Preferably, the acidic electrolyte includes H3PO4 and / or H2SO4; the clay includes one or more of Mg2H2(SiO3)3·3.0H2O, H2Al2O6Si·1.19H2O and H4Al2O9Si2·0.32H2O.
[0017] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention discloses a hydrogen solid-state secondary battery with a vanadium-based positive electrode. A vanadium-based compound is used as a positive electrode material in a new hydrogen solid-state secondary battery system. The assembled new hydrogen solid-state secondary battery has excellent cycle stability, high rate performance and low temperature performance, and has a wide range of applications. At the same time, the vanadium-based positive electrode materials of the present invention all have excellent specific capacity, which is beneficial to improving the specific capacity of the battery. Among them, the specific capacity of the battery prepared using the LiV3O8 positive electrode of the present invention can be as high as 292mAh / g. In addition, the preparation method of the vanadium-based positive electrode of the present invention is simple, consumes less energy, has low cost, is not limited by resources, is green and environmentally friendly, and is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0020] Figure 1 A schematic diagram showing the charging and discharging process of the hydrogen solid-state secondary battery assembled in Example 1;
[0021] Figure 2 This is a scanning electron microscope image of the Li3V2(PO4)3 positive electrode obtained in Example 1 magnified 50,000 times;
[0022] Figure 3 This is a scanning electron microscope image of the Li3V2(PO4)3 positive electrode obtained in Example 1 magnified 30,000 times;
[0023] Figure 4 This is a scanning electron microscope image of the Li3V2(PO4)3 positive electrode obtained in Example 1 magnified 20,000 times;
[0024] Figure 5 This is a scanning electron microscope image of the Li3V2(PO4)3 positive electrode obtained in Example 1 magnified 10,000 times;
[0025] Figure 6 X-ray element spectrum of the Li3V2(PO4)3 positive electrode obtained in Example 1 (the horizontal coordinate is the angle / °, and the vertical coordinate is the intensity / au);
[0026] Figure 7 The hydrogen solid-state secondary battery assembled in Example 1 is 0.05Ag -1 Cyclic performance and corresponding coulombic efficiency line graph under current density (the horizontal axis is the number of cycles, the vertical axis is the specific capacity / mAh·g -1 );
[0027] Figure 8 The hydrogen solid-state secondary battery assembled in Example 1 is 0.05Ag -1 Charge and discharge curves under current density (the horizontal position is specific capacity / mAh·g -1 , the ordinate is voltage / V);
[0028] Fig. 9 is the X-ray diffraction pattern of the solid electrolyte in Example 2 (the abscissa is angle / °, the ordinate is intensity / au);
[0029] Fig.10 The hydrogen solid-state secondary battery assembled in Example 2 is 0.05Ag -1 Charge and discharge curves under current density (the horizontal position is specific capacity / mAh·g -1 , the ordinate is voltage / V);
[0030] Fig.11 This is a schematic diagram of the charging and discharging process of the hydrogen solid-state secondary battery assembled in Example 4;
[0031] Fig.12 This is a scanning electron microscope image of the LiV3O8 positive electrode obtained in Example 4 magnified 50,000 times;
[0032] Fig.13 This is a scanning electron microscope image of the LiV3O8 positive electrode obtained in Example 4 magnified 30,000 times;
[0033] Fig.14 This is a scanning electron microscope image of the LiV3O8 positive electrode obtained in Example 4 magnified 20,000 times;
[0034] Fig.15 This is a scanning electron microscope image of the LiV3O8 positive electrode obtained in Example 4 magnified 10,000 times;
[0035] Fig.16 X-ray element spectrum of the LiV3O8 positive electrode obtained in Example 4 (the horizontal coordinate is the angle / °, and the vertical coordinate is the intensity / au);
[0036] Fig.17 The hydrogen solid-state secondary battery assembled in Example 4 is 0.1Ag -1 Cyclic performance and corresponding coulombic efficiency line graph under current density (the horizontal axis is the number of cycles, the vertical axis is the specific capacity / mAh·g -1 );
[0037] Fig.18 The hydrogen solid-state secondary battery assembled in Example 4 is 0.1Ag -1 Charge and discharge curves under current density (the horizontal position is specific capacity / mAh·g -1 , the ordinate is voltage / V);
[0038] Fig.19 The hydrogen solid-state secondary battery assembled in Example 5 is 0.1Ag -1 Charge and discharge curves under current density (the horizontal position is specific capacity / mAh·g -1 , the ordinate is voltage / V);
[0039] Fig. 20 This is a schematic diagram of the charging and discharging process of the hydrogen solid-state secondary battery assembled in Example 7;
[0040] Fig.21 This is a scanning electron microscope image of the LiVOPO4 positive electrode obtained in Example 7 magnified 50,000 times;
[0041] Fig. 22 This is a scanning electron microscope image of the LiVOPO4 positive electrode obtained in Example 7 magnified 30,000 times;
[0042] Fig.23 This is a scanning electron microscope image of the LiVOPO4 positive electrode obtained in Example 7 magnified 20,000 times;
[0043] Fig.24 This is a scanning electron microscope image of the LiVOPO4 positive electrode obtained in Example 7 magnified 10,000 times;
[0044] Fig.25 X-ray element spectrum of the LiVOPO4 positive electrode obtained in Example 7 (the horizontal coordinate is angle / °, and the vertical coordinate is intensity / au);
[0045] Fig.26 The hydrogen solid-state secondary battery assembled in Example 7 is 0.1Ag -1 Cyclic performance and corresponding coulombic efficiency line graph under current density (the horizontal axis is the number of cycles, the vertical axis is the specific capacity / mAh·g -1);
[0046] Fig. 27 The hydrogen solid-state secondary battery assembled in Example 7 is 0.1Ag -1 Charge and discharge curves under current density (the horizontal position is specific capacity / mAh·g -1 , the ordinate is voltage / V);
[0047] Fig.28 The hydrogen solid-state secondary battery assembled in Example 8 is 0.1Ag -1 Charge and discharge curves under current density (the horizontal position is specific capacity / mAh·g -1 , the vertical axis is voltage / V). DETAILED DESCRIPTION
[0048] The present invention provides a hydrogen solid-state secondary battery with a vanadium-based positive electrode, comprising a vanadium-based compound positive electrode, a Pt / C negative electrode and a solid electrolyte; the solid electrolyte comprises an acidic electrolyte and clay; the vanadium-based compound positive electrode comprises one of a Li3V2(PO4)3 positive electrode, a LiV3O8 positive electrode and a LiVOPO4 positive electrode.
[0049] In the present invention, the preparation method of the Li3V2(PO4)3 positive electrode comprises the following steps: mixing a vanadium source, a lithium source, a phosphate source and water, heating to obtain a gel-like mixture, and calcining the gel-like mixture to obtain a Li3V2(PO4)3 positive electrode.
[0050] In the present invention, the mass volume ratio of the vanadium source, lithium source, phosphoric acid source and water is 0.1-0.4g: 0.1-0.3g: 0.3-0.4g: 6-10mL, preferably 0.12-0.28g: 0.12-0.28g: 0.32-0.38g: 7-9mL, more preferably 0.15g: 0.15g: 0.35g: 8mL; the vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 The purity of the vanadium source is ≥99%, preferably 99.9%; the lithium source includes LiOH·H2O and / or LiNO3; the phosphate source includes one or more of NH4H2PO4 and (NH4)2HPO4.
[0051] In the present invention, the heating step is: mixing the vanadium source, the lithium source, the phosphate source and the water and heating to 70-100°C, preferably 75-95°C, more preferably 80-90°C, more preferably 85°C; keeping warm for 8-14h, preferably 9-13h, more preferably 11h; then adjusting to a vacuum environment, heating to 70-100°C, preferably 75-95°C, more preferably 80-90°C, more preferably 85°C; keeping warm for 8-14h, preferably 9-13h, more preferably 11h.
[0052] In the present invention, the calcination step is: heating the gel-like mixture to 300-500°C, preferably 350-450°C, more preferably 380-420°C, and more preferably 400°C; keeping it warm for 2-8h, preferably 3-7h, and more preferably 5h; then adjusting to argon atmosphere, heating to 700-950°C, preferably 750-900°C, more preferably 780-850°C, and more preferably 800°C; keeping it warm for 8-10h, preferably 8.2-9.7h, more preferably 8.5-9.2h, and more preferably 9h.
[0053] In the present invention, the preparation method of the LiV3O8 positive electrode comprises the following steps: mixing a vanadium source and a lithium source, and sequentially performing ball milling and calcination to obtain the LiV3O8 positive electrode.
[0054] In the present invention, the mass ratio of the vanadium source to the lithium source is 2-4:0.3-1, preferably 2.50-3.53:0.35-0.95, more preferably 2.8-3.0:0.45-0.55; the vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 One or more of the above; the lithium source includes LiOH·H2O and / or LiNO3.
[0055] In the present invention, the calcination temperature is 450-700°C, preferably 500-650°C, more preferably 550-600°C, and more preferably 555°C; the calcination time is 8-10h, preferably 8.2-9.8h, more preferably 8.5-9.3h, and more preferably 9h.
[0056] In the present invention, the preparation method of the LiVOPO4 positive electrode comprises the following steps: mixing a vanadium source, oxalic acid, a lithium source, a phosphoric acid source and water, and reacting to obtain a LiVOPO4 positive electrode.
[0057] In the present invention, the preparation method of the LiVOPO4 positive electrode preferably includes the following steps: firstly mixing a vanadium source, oxalic acid, a lithium source, a phosphoric acid source and water and heating them to obtain a green precursor, and then reacting the green precursor under air conditions to obtain a LiVOPO4 positive electrode.
[0058] In the present invention, the mass volume ratio of the vanadium source, oxalic acid, lithium source, phosphoric acid source and water is 0.5-1.2g:1.5-2.5g:0.2-1g:0.75-1.50g:100-150mL, preferably 0.58-1.10g:1.80-2.03g:0.25-0.83g:0.80-1.42g:110-140mL, more preferably 0.75-1.00g:1.85-1.93g:0.30-0.50g:0.95-1.36g:120-130mL; the vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 The purity of the vanadium source is ≥99%, preferably 99.9%; the lithium source includes LiOH·H2O and / or LiNO3; the phosphate source includes one or more of NH4H2PO4 and (NH4)2HPO4.
[0059] In the present invention, the heating temperature is preferably 70-100°C, more preferably 80-90°C, more preferably 85°C; the heating time is preferably 8-12h, more preferably 10h; the reaction temperature is 350-550°C, preferably 400-500°C, more preferably 450°C; the reaction time is 8-10h, preferably 8.2-9.8h, more preferably 8.5-9.3h, more preferably 9h.
[0060] In the present invention, the mass ratio of the acidic electrolyte to the clay in the solid electrolyte is 0.5-1.5:1-5, preferably 0.8-1.2:2-4, and more preferably 1:3; the Pt in the Pt / C negative electrode accounts for 15% to 50% of the total mass of the Pt / C negative electrode, preferably 20% to 45%, further preferably 30% to 40%, and more preferably 32%.
[0061] In the present invention, the volume concentration of the acidic electrolyte is 10% to 85%, preferably 20% to 70%, more preferably 35% to 55%, and even more preferably 45%.
[0062] In the present invention, the acidic electrolyte includes H3PO4 and / or H2SO4; the clay includes one or more of Mg2H2(SiO3)3·3.0H2O, H2Al2O6Si·1.19H2O and H4Al2O9Si2·0.32H2O.
[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0064] Example 1
[0065] First, prepare the Li3V2(PO4)3 positive electrode by dissolving 0.1819g of V2O5 (purity of 99.9%), 0.345g of NH4H2PO4 and 0.1258g of LiOH·H2O in 8mL of deionized water and stirring the mixture continuously at room temperature to obtain a mixed solution. The mixed solution is then transferred to a hydrothermal autoclave, heated to 70°C and kept warm for 12h, then heated to 90°C under vacuum conditions and kept warm for 10h to obtain a gel-like mixture. Finally, the gel-like mixture is heated to 350°C and kept warm for 4h, then heated to 850°C under a flowing argon atmosphere and kept warm for 10h to obtain the Li3V2(PO4)3 positive electrode.
[0066] Then, the positive electrode sheet, the Pt / C negative electrode sheet and the solid electrolyte membrane are prepared.
[0067] The preparation method of the positive electrode sheet is as follows: the positive electrode active material Li3V2(PO4)3, the conductive agent acetylene black and the binder PTFE are rolled into a film in a ratio of 7:2:1 to form an electrode, wherein the current collector is a titanium mesh and the active material loading is 5 mg cm -2 , the diameter of the positive electrode is 19mm.
[0068] The preparation method of the Pt / C negative electrode sheet is as follows: Pt / C negative electrode catalyst powder and binder PTFE are rolled into a film in a ratio of 8:2 to form an electrode, wherein the current collector is a titanium mesh and the Pt loading is 1 mg cm -2 The diameter of the Pt / C negative electrode piece is 19 mm; Pt in the Pt / C negative electrode accounts for 40% of the total mass of the Pt / C negative electrode.
[0069] The preparation method of the solid electrolyte membrane is as follows: bentonite H2Al2O6Si·1.19H2O and acidic electrolyte H3PO4 are mixed in a mass ratio of 1:1 to prepare a gel-like solid electrolyte membrane, wherein the volume concentration of the acidic electrolyte H3PO4 is 63%.
[0070] Finally, assemble the battery. The assembly order of the battery is: positive electrode plate, solid electrolyte membrane and Pt / C negative electrode plate.
[0071] The charging and discharging process principle of the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in Example 1 is as follows Figure 1 As shown, during the first charging process, the positive electrode material Li3V2(PO4)3 releases Li + The protons in the solid electrolyte membrane react to generate hydrogen under the catalysis of the negative electrode catalyst Pt. During the discharge process, the hydrogen reacts on the negative electrode catalyst Pt to generate protons that are transferred to the solid electrolyte and then embedded into the positive electrode material V2(PO4)3 through the Grotthuss mechanism to generate H xV2(PO4)3. In the second and subsequent charge and discharge processes, the positive electrode is the proton embedding in V2(PO4)3 (discharge process) and the proton embedding in H x During the release (charging process) of V2(PO4)3, the oxidation and reduction reactions of protons occur at the negative electrode.
[0072] After testing, the scanning electron microscope image of the Li3V2(PO4)3 positive electrode in this embodiment 1 is as follows Figures 2 to 5 As shown, from Figures 2 to 5 It can be seen that the Li3V2(PO4)3 positive electrode presents a layered stacking structure with a width of 1.5 to 2.5 μm, which is more conducive to the embedding and extraction of protons. The positive electrode material can maintain a good structure during the embedding and extraction reaction of protons, and the structure is not easy to collapse, providing better electrochemical performance. That is, the Li3V2(PO4)3 positive electrode material prepared in Example 1 presents a layered stacking structure, which is conducive to improving the specific capacity of the material, thereby making the battery have a higher specific capacity; the X-ray element spectrum is as follows Figure 6 As shown, from Figure 6 It can be seen that pure phase Li3V2(PO4)3 was successfully synthesized in this embodiment.
[0073] The hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment is still at 0.05Ag. -1 The cycle performance and corresponding coulombic efficiency tests were carried out at a current density of Figure 7 As shown, from Figure 7 It can be seen that the specific capacity of the battery is 160.83 mAh / g. After 130 cycles, the specific capacity of the battery only decays by 95.68 mAh / g. It is expected that the battery can be cycled for more than 10,000 cycles. In addition, the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment has a specific capacity of 160.83 mAh / g. -1 The charge and discharge curves at current density are shown in Figure 8 As shown, from Figure 8 It can be seen that the voltage range of charge and discharge is between 0.2 and 1.5V.
[0074] When charging, the positive electrode of the hydrogen solid-state secondary battery with a vanadium-based positive electrode assembled in this embodiment releases lithium ions and the negative electrode generates hydrogen; when discharging, the negative electrode hydrogen is oxidized into protons, and the lithium ions and protons are embedded in the positive electrode material. The chemical reaction is as follows:
[0075] Cathode: Step 1: Li3V2(PO4)3–3e - =V2(PO4)3+3Li +
[0076] Step 2: V2(PO4)3+xH + +xe - =Hx V2(PO4)3
[0077] Negative electrode: x / 2H2=xH + +xe -
[0078] Overall reaction: V2(PO4)3+x / 2H2=H x V2(PO4)3
[0079] Example 2
[0080] First, prepare the Li3V2(PO4)3 positive electrode by dissolving 0.1499g of V2O3 (purity of 99.9%), 0.345g of (NH4)2HPO4 and 0.2068g of LiNO3 in 8mL of deionized water and stirring the mixture continuously at room temperature to obtain a mixed solution. The mixed solution is then transferred to a hydrothermal autoclave, heated to 70°C and kept for 12h, then heated to 90°C under vacuum conditions and kept for 10h to obtain a gel-like mixture. Finally, the gel-like mixture is heated to 350°C and kept for 4h, then heated to 850°C under a flowing argon atmosphere and kept for 10h to obtain the Li3V2(PO4)3 positive electrode.
[0081] Then, a hydrogen solid-state secondary battery with a vanadium-based positive electrode is assembled by using the same preparation process and battery assembly process of the positive electrode sheet, the Pt / C negative electrode sheet and the solid electrolyte membrane as in Example 1. Among them, there are the following differences between Example 2 and Example 1: the solid electrolyte is H3PO4 and sepiolite Mg2H2(SiO3)3·3.0H2O in a mass ratio of 1:1; the volume concentration of the acidic electrolyte H3PO4 is 63%; and the Pt in the Pt / C negative electrode accounts for 20% of the total mass of the Pt / C negative electrode.
[0082] After testing, the X-ray diffraction pattern of the solid electrolyte in the hydrogen solid secondary battery with vanadium-based positive electrode assembled in Example 2 is as follows: Fig. 9 As shown, from Fig. 9 It can be seen that the addition of phosphoric acid does not change the structure of sepiolite. In addition, the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment has a 0.05Ag -1 The charge and discharge curves at current density are shown in Fig.10 As shown, from Fig.10 It can be seen that the voltage range of charge and discharge is between 0.2 and 1.5V.
[0083] Example 3
[0084] First, prepare the Li3V2(PO4)3 positive electrode by dissolving 0.1659g of VO2 (purity of 99.9%), 0.345g of NH4H2PO4 and 0.1258g of LiOH·H2O in 8mL of deionized water and stirring the mixture at room temperature to obtain a mixed solution. The mixed solution is then transferred to a hydrothermal autoclave, heated to 70°C and kept for 12h, then heated to 90°C under vacuum conditions and kept for 10h to obtain a gel-like mixture. Finally, the gel-like mixture is heated to 350°C and kept for 4h, then heated to 850°C under a flowing argon atmosphere and kept for 10h to obtain the Li3V2(PO4)3 positive electrode.
[0085] Then, a hydrogen solid-state secondary battery with a vanadium-based positive electrode is assembled by using the same preparation process and battery assembly process of the positive electrode sheet, the Pt / C negative electrode sheet and the solid electrolyte membrane as in Example 1. Among them, there are the following differences between this Example 3 and Example 1: the solid electrolyte is H3PO4 and bentonite H4Al2O9Si2·0.32H2O in a mass ratio of 1:1; the volume concentration of the acidic electrolyte H3PO4 is 63%; and the Pt in the Pt / C negative electrode accounts for 20% of the total mass of the Pt / C negative electrode.
[0086] Example 4
[0087] First, a LiV3O8 positive electrode was prepared by ball milling 2.67 g of V2O3 (purity of 99.9%) and 0.53 g of LiOH·H2O in a ball mill for 10 min, and then heating to 600°C in air and keeping the temperature for 10 h to obtain a LiV3O8 positive electrode.
[0088] Then, the preparation process of the positive electrode sheet, the Pt / C negative electrode sheet and the solid electrolyte membrane and the battery assembly process which are completely the same as those in Example 1 are used to assemble a hydrogen solid-state secondary battery with a vanadium-based positive electrode.
[0089] The charging and discharging process principle of the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in Example 4 is as follows Fig.11 As shown, during charging, the positive electrode releases lithium ions and the negative electrode produces hydrogen; during discharging, protons are embedded in the positive electrode material and the negative electrode hydrogen is oxidized into protons.
[0090] After testing, the scanning electron microscope image of the LiV3O8 positive electrode in this embodiment 4 is as follows Figures 12 to 15 As shown, from Figures 12 to 15 It can be seen that the LiV3O8 positive electrode presents a carbon nanorod structure with a width of 1.5 to 2.5 μm. It has a stable structure, which is conducive to the embedding and extraction of protons and is not easily destroyed. It is also conducive to improving the specific capacity of the material, thereby making the battery have a higher specific capacity; the X-ray element spectrum is shown in Fig.16 As shown, from Fig.16It can be seen that pure phase LiV3O8 was successfully synthesized in this embodiment.
[0091] The hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment is still at 0.1Ag. -1 The cycle performance and corresponding coulombic efficiency tests were carried out at a current density of Fig.17 As shown, from Fig.17 It can be seen that the specific capacity of the battery is 292 mAh / g. After 30 cycles, the specific capacity of the battery can still be maintained above 100 mAh / g. It is expected that the battery can be cycled for more than 10,000 cycles. In addition, the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment has a specific capacity of 292 mAh / g. -1 The charge and discharge curves at current density are shown in Fig.18 As shown, from Fig.18 It can be seen that the voltage range of charge and discharge is between 0.3 and 1.6V.
[0092] The chemical reaction of the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment is as follows:
[0093] Positive electrode: First step: LiV3O8–e - =V3O8+Li +
[0094] Step 2: V3O8+xH + +xe - =H x V3O8
[0095] Negative electrode: x / 2H2=xH + +xe -
[0096] Overall reaction: V3O8+x / 2H2=H x V3O8
[0097] Example 5
[0098] First, a LiV3O8 positive electrode was prepared by ball milling 3.25 g of V2O5 (purity of 99.9%) and 0.87 g of LiNO3 in a ball mill for 10 min, and then heated to 600°C in air and kept warm for 10 h to obtain a LiV3O8 positive electrode.
[0099] Then, a hydrogen solid-state secondary battery with a vanadium-based positive electrode is assembled by using the same preparation process and battery assembly process of the positive electrode sheet, the Pt / C negative electrode sheet and the solid electrolyte membrane as in Example 4. Among them, there are the following differences between this Example 5 and Example 4: the solid electrolyte is H3PO4 and sepiolite Mg2H2(SiO3)3·3.0H2O (same as the sepiolite in Example 2) in a mass ratio of 1:1; the volume concentration of the acidic electrolyte H3PO4 is 63%; and Pt in the Pt / C negative electrode accounts for 40% of the total mass of the Pt / C negative electrode.
[0100] After testing, the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment has a -1 The charge and discharge curves at current density are shown in Fig.19 As shown, from Fig.19 It can be seen that the voltage range of charge and discharge is between 0.3 and 1.6V.
[0101] Example 6
[0102] First, a LiV3O8 positive electrode was prepared by ball milling 3.15 g of V3O7 (purity of 99.9%) and 0.53 g of LiOH·H2O in a ball mill for 10 min, and then heating to 600°C in air and keeping the temperature for 10 h to obtain a LiV3O8 positive electrode.
[0103] Then, a hydrogen solid-state secondary battery with a vanadium-based positive electrode is assembled by using the same preparation process and battery assembly process of the positive electrode plate, the Pt / C negative electrode plate and the solid electrolyte membrane as in Example 4. Among them, there are the following differences between this Example 6 and Example 4: the solid electrolyte is H3PO4 and bentonite H4Al2O9Si2·0.32H2O (the same bentonite in Example 3) in a mass ratio of 1:1; the volume concentration of the acidic electrolyte H3PO4 is 63%; and Pt in the Pt / C negative electrode accounts for 40% of the total mass of the Pt / C negative electrode.
[0104] Example 7
[0105] First, prepare the LiVOPO4 positive electrode. Dissolve 0.75g of V2O3 (purity of 99.9%) and 1.9g of oxalic acid in 100mL of deionized water, then add 1.15g of NH4H2PO4 and 0.725g of LiNO3 in sequence, heat to 90℃ and keep warm for 10h to obtain a green precursor, and finally heat the green precursor to 500℃ under air conditions and keep warm for 10h to obtain a LiVOPO4 positive electrode.
[0106] Then, the preparation process of the positive electrode plate, the Pt / C negative electrode plate and the solid electrolyte membrane and the battery assembly process which are exactly the same as those in Example 1 are used to assemble a hydrogen solid-state secondary battery with a vanadium-based positive electrode.
[0107] The charging and discharging process principle of the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in Example 7 is as follows Fig. 20 As shown, during charging, the positive electrode releases lithium ions and the negative electrode produces hydrogen; during discharging, protons are embedded in the positive electrode material and the negative electrode hydrogen is oxidized into protons.
[0108] After testing, the scanning electron microscope image of the LiVOPO4 positive electrode in this embodiment 7 is as follows Figures 21 to 24 As shown, from Figures 21 to 24 It can be seen that the LiVOPO4 positive electrode presents a porous structure with a width of 1.5 to 2.5 μm. The porous structure is more conducive to the embedding and extraction of protons, and is also conducive to improving the specific capacity of the material, thereby making the battery have better performance; the X-ray element spectrum is shown in Fig.25 As shown, from Fig.25 It can be seen that pure phase LiVOPO4 was successfully synthesized in this embodiment.
[0109] The hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment is still at 0.1Ag. -1 The cycle performance and corresponding coulombic efficiency tests were carried out at a current density of Fig.26 As shown, from Fig.26 It can be seen that the specific capacity of the battery is 187.6 mAh / g. After 50 cycles, the specific capacity of the battery only decays by 122.1 mAh / g. It is expected that the battery can be cycled for more than 10,000 cycles. In addition, the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment has a specific capacity of 187.6 mAh / g. -1 The charge and discharge curves at current density are shown in Fig. 27 As shown, from Fig. 27 It can be seen that the voltage range of charge and discharge is between 0.2 and 1.6V.
[0110] The chemical reaction of the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment is as follows:
[0111] Cathode: Step 1: LiVOPO4–e - =VOPO4+Li +
[0112] Step 2: VOPO4+xH + +xe - =H x VOPO4
[0113] Negative electrode: x / 2H2=xH + +xe -
[0114] Overall reaction: VOPO4+x / 2H2=H x VOPO4
[0115] Example 8
[0116] First, prepare the LiVOPO4 positive electrode. Dissolve 0.91g of V2O5 (purity of 99.9%) and 1.9g of oxalic acid in 100mL of deionized water, then add 1.15g of (NH4)2HPO4 and 0.441g of LiOH·H2O in sequence, heat to 90℃ and keep warm for 8h to obtain a green precursor, and finally heat the green precursor to 500℃ under air conditions and keep warm for 10h to obtain a LiVOPO4 positive electrode.
[0117] Then, a hydrogen solid-state secondary battery with a vanadium-based positive electrode is assembled by using the same preparation process and battery assembly process of the positive electrode plate, the Pt / C negative electrode plate and the solid electrolyte membrane as in Example 7. Among them, there are the following differences between this Example 8 and Example 7: the solid electrolyte is H3PO4 and sepiolite Mg2H2(SiO3)3·3.0H2O (same as the sepiolite in Example 2) in a mass ratio of 1:1; the volume concentration of the acidic electrolyte H3PO4 is 63%; and Pt in the Pt / C negative electrode accounts for 40% of the total mass of the Pt / C negative electrode.
[0118] After testing, the hydrogen solid-state secondary battery with vanadium-based positive electrode assembled in this embodiment has a -1 The charge and discharge curves at current density are shown in Fig.28 As shown, from Fig.28 It can be seen that the voltage range of charge and discharge is between 0.2 and 1.6V.
[0119] Example 9
[0120] First, prepare the LiVOPO4 cathode by mixing 0.85 g of V6O 13 (purity of 99.9%) and 1.9 g of oxalic acid were dissolved in 100 mL of deionized water, and then 1.15 g of NH4H2PO4 and 0.441 g of LiOH·H2O were added in sequence, heated to 90°C and kept warm for 8 h to obtain a green precursor, and finally the green precursor was heated to 500°C under air conditions and kept warm for 10 h to obtain a LiVOPO4 positive electrode.
[0121] Then, a hydrogen solid-state secondary battery with a vanadium-based positive electrode is assembled by using the same preparation process and battery assembly process of the positive electrode plate, the Pt / C negative electrode plate and the solid electrolyte membrane as in Example 7. Among them, there are the following differences between this Example 9 and Example 7: the solid electrolyte is H3PO4 and bentonite H4Al2O9Si2·0.32H2O (the same bentonite in Example 3) in a mass ratio of 1:1; the volume concentration of the acidic electrolyte H3PO4 is 63%; and Pt in the Pt / C negative electrode accounts for 40% of the total mass of the Pt / C negative electrode.
[0122] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hydrogen solid-state secondary battery with a vanadium-based positive electrode, characterized in that: The vanadium-based positive electrode hydrogen solid-state secondary battery comprises a vanadium-based compound positive electrode, a Pt / C negative electrode and a solid electrolyte; The solid electrolyte includes an acidic electrolyte and clay; The vanadium-based compound positive electrode includes one of a Li3V2(PO4)3 positive electrode, a LiV3O8 positive electrode and a LiVOPO4 positive electrode.
2. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 1, characterized in that: The preparation method of the Li3V2(PO4)3 positive electrode comprises the following steps: After mixing a vanadium source, a lithium source, a phosphoric acid source and water, heating is performed to obtain a gel-like mixture, and the gel-like mixture is calcined to obtain a Li3V2(PO4)3 positive electrode.
3. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 2, characterized in that: The mass volume ratio of the vanadium source, the lithium source, the phosphoric acid source and water is 0.1-0.4 g: 0.1-0.3 g: 0.3-0.4 g: 6-10 mL; The vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 One or more of the following; The lithium source includes LiOH·H2O and / or LiNO3; The phosphoric acid source includes one or more of NH4H2PO4 and (NH4)2HPO4; The heating step comprises: mixing the vanadium source, the lithium source, the phosphoric acid source and the water, heating the mixture to 70-100° C., keeping the mixture warm for 8-14 hours, and then adjusting the mixture to a vacuum environment, heating the mixture to 70-100° C., and keeping the mixture warm for 8-14 hours; The calcination step is: heating the gel mixture to 300-500° C., keeping the temperature for 2-8 hours, then adjusting to an argon atmosphere, heating to 700-950° C., and keeping the temperature for 8-10 hours.
4. The hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 1, characterized in that: The preparation method of the LiV3O8 positive electrode comprises the following steps: The vanadium source and the lithium source are mixed, ball-milled and calcined in sequence to obtain the LiV3O8 positive electrode.
5. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 4, characterized in that: The mass ratio of the vanadium source to the lithium source is 2-4:0.3-1; The vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 One or more of the following; The lithium source includes LiOH·H2O and / or LiNO3; The calcination temperature is 450-700° C. and the calcination time is 8-10 hours.
6. The hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 1, characterized in that: The preparation method of the LiVOPO4 positive electrode comprises the following steps: A vanadium source, oxalic acid, a lithium source, a phosphoric acid source and water are mixed and reacted to obtain a LiVOPO4 positive electrode.
7. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 6, characterized in that: The mass volume ratio of the vanadium source, oxalic acid, lithium source, phosphoric acid source and water is 0.5-1.2g:1.5-2.5g:0.2-1g:0.75-1.50g:100-150mL; The vanadium source includes V2O3, V2O5, VO2, V3O7 and V6O 13 One or more of the following; The lithium source includes LiOH·H2O and / or LiNO3; The phosphoric acid source includes one or more of NH4H2PO4 and (NH4)2HPO4; The reaction temperature is 350-550° C. and the reaction time is 8-10 hours.
8. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to any one of claims 1 to 7, characterized in that: The mass ratio of the acidic electrolyte to the clay in the solid electrolyte is 0.5-1.5:1-5; The Pt in the Pt / C negative electrode accounts for 15% to 50% of the total mass of the Pt / C negative electrode.
9. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 8, characterized in that: The volume concentration of the acid electrolyte is 10% to 85%.
10. A hydrogen solid-state secondary battery with a vanadium-based positive electrode according to claim 9, characterized in that: The acidic electrolyte includes H3PO4 and / or H2SO4; The clay includes one or more of Mg2H2(SiO3)3·3.0H2O, H2Al2O6Si·1.19H2O and H4Al2O9Si2·0.32H2O.
